Resilience and sense of belonging among medical students in a Malaysian public university - Ali, Sallehudin; Amat, Salleh; Mahmud, Mohd Izwan; Abidin, Mohd Hakimie Zainal; Subhan, Mhd; Bakar, Abu Yazid Abu (International Journal of Engineering and Technology, 2018)
Medical programs have always been regarded as highly difficult and highly stressful professional programs when compared to other programs. Medical students need to be resilient because the programs are full of adversity that can bring stress and tension to themselves. The purpose of this study is to examine the level of resilience and sense of belonging among medical students. Respondents of this study consisted of 137-year three medical students. Two sets of questionnaires were used in this study; Brief Resilience Scale (BRS) and Sense of Belonging Instrument-Psychological (SOBI-P). The findings from this research show the level of resilience among medical students is considered as moderately high while sense of belonging level is high. The implications of this study on student’s development and counselor’s roles in higher learning institutions will also be discussed.